Advances in Green Synthesis and Photo-/Electrocatalytic Applications of Zirconium-Based MOFs: A Review - Tian Zhao; Shilin Peng; Jiangrong Yu; Jiayao Chen; Fuli Luo; Pengcheng Xiao; Saiqun Nie; Yi Chen (Organics, 2025)
Metal–organic frameworks (MOFs), particularly zirconium-based frameworks (Zr-MOFs), have gained significant attention in recent years due to their unique structural and functional properties. This review focuses on eco-friendly synthetic methods for producing Zr-MOFs, addressing the environmental impacts and costs associated with conventional synthesis, which often relies on hazardous reagents and harsh conditions. We explore various green synthesis strategies, including the selection of raw materials (such as using zirconium acetate), organic ligands (recycling waste materials for ligand synthesis), and synthesis methods (solvothermal, microwave-assisted, ultrasound-assisted, electrochemical, and mechanochemical approaches). Additionally, the application of Zr-MOFs in photocatalysis and electrocatalysis is examined, highlighting their potential for environmental purification and energy conversion. Despite the progress made in laboratory settings, challenges remain in achieving cost-effectiveness, material stability, and scalability for industrial applications. Future research should concentrate on enhancing synthesis efficiency, optimizing catalytic properties, investigating structure–property relationships, and expanding applications to novel catalytic reactions, thus ensuring Zr-MOFs can contribute to sustainable development in chemical science and technology.